Association between smoking and hypertension under different PM2.5 and green space exposure: A nationwide cross-sectional study - Chen, Qihao; Ma, Xuxi; Geng, Yan; Liao, Jingling; Ma, Lu (Frontiers in Public Health, 2022)
Background: Smoking has been widely reported as a risk factor for hypertension, but there is still a lack of studies to discuss the effect of environmental exposure on the relationship between smoking and hypertension. Therefore, this study estimated the association between smoking and hypertension in middle aged and elderly people in China under different PM2.5 (fine particulate matter) and surrounding greenness exposure condition. Methods: Individual sample data from the China Health and Retirement Longitudinal Study in 2018 and long-term average exposure concentration of fine particles and surrounding greenness exposure for all participants were used with the binary logistic regression model. Adjustments were made for sociodemographic characteristics and other health behaviors including drinking, physical activity, and social activity. Analysis was also stratified using gender and age group. Results: A total of 10600 participants over the age of 45 were included in the study. The effects of smoking on hypertension were diverse under different environmental exposure conditions. After long-term exposure to low NDVI, the hypertension risk of current and former smokers increased by at least 58.0% and 68.9% respectively compared with those who never smoked, and the hypertension risk of current and former smokers long-term exposed to high concentration of PM2.5 increased by at least 12.3% and 31.7% respectively. Among participants long-term exposed to both low green space and high concentration of PM2.5, the hypertension risk of current and former smokers increased by 66.7% and 82.5% respectively. In the subgroup analysis, the increased risk of hypertension caused by smoking due to the deterioration of green space and fine particle exposure conditions was more significant in males and participants aged 45-64 years Conclusions: Exposure to high concentration of PM2.5 or low green space may strengthen the association between smoking and hypertension risk, and this association was rapidly significant when participants were exposed to both.